2024
DOI: 10.28924/2291-8639-22-2024-45
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Investigation for Two-Bacteria Competition in Presence of a Pathogen With Leachate Recirculation

Miled El Hajji,
Adnan Y. Al-Subhi,
Mohammed H. Alharbi

Abstract: This paper provides a thorough exploration of two-species competition in a continuous bioreactor when adding a pathogen that affects only one species and with leachate recirculation inside the reactor. The dynamics is modelled by a well-constructed system of nonlinear differential equations extending the classical model of the chemostat by adding more realism, enhancing its applicability. The nonnegativity and boundedness of trajectories, the determination of steady states and their local stability strengthens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…It can be easily shown that W 0 = {E 0 } . Applying LaSalle's invariance principle [33] (see [34] for other applications), we deduce that E 0 is GAS when R 0 ≤ 1.…”
Section: Global Properties Of Steady Statesmentioning
confidence: 92%
“…It can be easily shown that W 0 = {E 0 } . Applying LaSalle's invariance principle [33] (see [34] for other applications), we deduce that E 0 is GAS when R 0 ≤ 1.…”
Section: Global Properties Of Steady Statesmentioning
confidence: 92%
“…We apply the next-generation matrix method introduced by Diekmann [23,24] to calculate the basic reproduction number for our system (3.2). See [25][26][27][28][29][30] for other applications. Let us define the matrices F and V by…”
Section: Numerical Examplesmentioning
confidence: 99%
“…The basic reproduction number was approximated by using the next generation matrix method [29][30][31]. See [2,[32][33][34][35][36] for other applications. Let us consider the matrices…”
Section: Numerical Simulationsmentioning
confidence: 99%